SCREENING OF METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) FROM SPUTUM SAMPLES - PRIYANKA SHARMA (International Journal of Pharma and Bio Sciences, 2014)
Staphylococcal infections are a group of infections caused by the bacterium Staphylococcus but most infections are caused by a type called Staphylococcus aureus. Bacteria are constantly evolving because their genes are constantly changing. The result of this is that some of the bacteria develop more resistance to a certain antibiotic than others. Methicillin-resistant Staphylococcus aureus is a strain of Staphylococcus aureus who developed resistance to methicillin and is responsible for several infections in humans which cannot be treated easily. It is resistant to many antibiotics and is called as multidrug-resistant Staphylococcus aureus and oxacillin-resistant Staphylococcus aureus. MRSA have resistance because of the widespread use of antibiotics, genetic selection and our dislike of tablets. Most MRSA infections are skin infections but it is also responsible for life-threatening bloodstream infections, pneumonia and surgical site infections. In the present study, a total number of 21 respiratory/sputum samples were collected and screened for methicillin resistant Staphylococcus aureus by biochemical and antibiotic sensitivity tests. Out of 21 samples, 10 were observed as methicillin resistant Staphylococcus aureus. It was found that MRSA shows highly variable antibiotic resistance. All MRSA shows 100% resistance to penicillin but were recorded sensitive to vancomycin. Thus penicillin and methicillin were not found to be effective against MRSA. The study suggests that vancomycin may be used as the drug of choice for treating multidrug resistant MRSA infections.